Achieving equity in education requires systemic change. Issue 10 (17th November 2020) - Hope, Joan
Abstract : Creating equity in opportunities and outcomes in education has been a perpetual challenge. Panelists for "Opening the Door to Equity in Education, " a webinar hosted by the National Student Clearinghouse, described how COVID‐19 has highlighted the challenges and how data can help guide a way to solutions.